Constitucionalismo internacional: direitos humanos sob a ótica da globalização - Bezerra Junior, Jose Albenes (2010)
The work presented here is the result of research on the issue of human rights in the face of conflicting issues such as the incorporation of international treaties, the sovereignty of states, globalization and multuculturalism. Specifically, we will investigate the origin of human rights, alongside his growing recognition, from the Revolutions until its completion in the Universal Declaration of Human Rights in 1948. The question, however, has become broader, when analyzed from the perspective of the internationalization of these rights as conditions and limits of democracy. Given the convergence on the reception of international treaties on human rights, we analyze a series of positions, including recent placements of the Supreme Court, and Constitutional Amendment n.45/2004. The study aims to review the classical concept of sovereignty, now within a new perspective based on the appearance of certain limitations of the state and a crisis in the face of the protection of human rights. We analyze the phenomenon of globalization in light of its complexity and its relation to sovereignty and human rights in pursuit of an expansion of democracy. The theme is consistent also with the line of contemporary constitutionalism, since their approach has a close connection with the issues of sovereignty and globalization, as well as a current relationship with the protection of human rights. The research aims to analyze the formation of a new society within a global vision of the constitutionalization of international law. It seeks to glimpse the invocacion model of foreign precedents and the possibility of dialogue betweem States as a way of protecting and enforcing the protection of human rights